Implications of the Novel Mutations in the SARS-CoV-2 Genome for Transmission, Disease Severity, and the Vaccine Development - Akkiz, Hikmet (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) , the causative agent of the coronavirus disease 2019 (COVID-19), is steadily mutating during its continuous transmission among humans. During the COVID-19 pandemic, SARS-CoV-2 has accumulated mutations throughout viral genes encoding the ORF1a, ORF1b, ORF3, ORF8, nucleocapsid (N) and Spike (S) proteins. Mutations in the S protein are especially crucial because the S protein is key for the first step of viral transmission. A novel isolate of SARS-CoV-2 virus carrying the spike protein amino acid change D614G recently emerged and rapidly became dominant around the world. The consistent increase of the G614 variant at regional levels shows that the variant may have a fitness advantage. The spike protein D614G mutation increases SARS-CoV-2 infection in multiple human cell types. In addition, clinical samples obtained from COVID-19 patients carrying G614 variant have a higher levels of viral RNA. Although clinical and in vitro data suggest that the spike protein D614G mutation changes the virus phenotypically, the impact of the mutation on the rate of transmission between people, disease severity and the vaccine and therapeuticdevelopment is controversial. The review discusses the effects of novel mutations in the SARS-CoV-2 genome on the transmission, the clinical outcomes and vaccine and drug development.